Услуги современных цифровых сетей интегрального обслуживания (ISDN) для дистанционного обучения - Сабурова, С. А. (УАДО, 2004)
For successful development of the distance learning system it is necessary to take into account possibilities of the up-to-date technologies, functioning at the communication networks of Ukraine. Presently, when international network Internet has entered our everyday life, and need in loading of multimedia files has emerged, interest to ISDN services and subscriber high-speed access has been arisen.
Keywords: услуги цифровых сетей; дистанционное обучение